IN VITRO STUDIES TO ASSESS THE ANTIDIABETIC POTENTIAL OF SCHLEICHERA OLEOSA (LOUR) OKEN LEAVES - Muthukrishnan, Soundararajan; T, Sivakkumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Objective: The aim of this research is to establish the antidiabetic properties of sequential extracts of Schleichera oleosa (lour) Oken leaves thru Î±-amylase and Î±-glucosidase inhibitory assay. Methods: The extracts of S. oleosa (Lour) Oken were prepared by continuous hot percolating the dried powder of the plant leaves. The various solvents were used for the extraction and qualitative assay for the phytochemical test using standard protocols. Different concentration (1, 2, 4, 6, 12, 25, and 50 mg/ml) of sequential extracts of S. oleosa leaves were used to assess the in vitro Î±-amylase and Î±-glucosidase inhibitory assay by Bernfeld and Apostolidis method. Results: In the Î±-amylase assay, the ethanolic extract produced 52.76% inhibition at 4 mg/ml concentration, but in ethyl acetate and aqueous extracts case 50% inhibition attained only at the concentration of 50 mg/ml, and acarbose 0.9 mg/ml was found 89.24% inhibition. In the Î±-glucosidase assay, the all extracts show the decent inhibitory effect in 50 mg/ml. The ethanolic and aqueous extracts exhibited a higher inhibitory effect 72.64% and 59.44% than other extracts at the concentration of 50 mg/ml, respectively, while acarbose 0.9 mg/ml was producing 86.24% inhibition. This result indicates that the inhibition of ethanolic and aqueous extracts on the activity from Î±-amylase and Î±-glucosidases is much more potent than that of other extracts. Conclusion: This study revealed that ethanolic and aqueous extracts showed the high content of polyphenols and flavonoids, which was blamed for the Î±-amylase and Î±-glucosidases inhibition. Hence, it deserved to elucidate specific components and to evaluate the antidiabetic effect using in vivo animal model.